Performance evaluation of a low cost modular solar desalination and disinfection chamber - Tolosa, Nolan C. (2006)
The low cost water desalination or solar still was designed and fabricated to reduce and eleiminate microbiological and chemical pollutants. The following parameters were used to determine the efficacy of treatment of saline water-total and fecal coliforms, biological oxygen demand (BOD5), chemical oxygen demand, (COD), chloride, color, conductivity, pH, total dissolved solids (TDS), turbidity, hardness, sulfate, and selected metals such as cadmium, chromium, copper, iron, lead and manganese. The 10-liter capacity Solar Desalination and Disinfection Chamber (SDDC) set-up consisted of 12.7 mm thick glass with dimensions of 0.9 x 0.9 x 1.2 m. The SDDC was also equipped with thermocouple, cloth filtration as pretreatment and activated carbon for final treatment. This was made to determine the pathogen (total and fecal coliform) and chloride reduction of the saline water feed. Other parameters such as TDS, color, BOD5, COD, conductivity, pH, turbidity, hardness, sulfate, cadmium, chromium, copper, iron, lead and manganese were also analyzed. The SDDC prototype had the capacity to disinfect contaminated water with initial value of ≥16x10 6 MPN/100 mL for total and fecal coliform achieving a value of < 2 MPN/100 mL. Another important result was the reduction of chlorides from saline water with initial values from 14,000 mg/L to 19,000 mg/L to 1.0 mg/L. This is the main factor that contributes to the salinity of the water. The volume of treated water ranged from 230 mL to 3,270 mL per day, depending on sunlight exposure and cloud cover. The measured optimum temperature ranged from 34̊C to 67 ̊C for an 8-hr exposure to the sun. The true color of the saline water sample with initial values that ranged from 86 PCU to 115 PCU obtained a negligible value to 2 PCU of color after treatment, giving a 98% - 100% color removal. Solar desalination is economically attractive since the energy used is free and renewable unlike for other conventional desalination processes. The cost estimation for a liter production was PhP 4.75 for SDDC and PhP 9.75 for flash distillation.